A Biography of the ’intellettuale impegnato’: Italo Calvino - Pilz, Kerstin (Spunti e Ricerche, 2016)
This article offers a broad overview of the author’s complex itinerary, exploring the extent to which the variation in Calvino’s narrative style was the result of his attempt to redefine the role of literature in a changing society. The author explains that in the early years of his career the search for a new literature was motivated by his juvenile belief that a new literary style would serve the construction of a new society. This certainty, tied to the writer’s belief in the power of politics and his self-image as writer engagé, as "intellettuale impegnato," that is to say, as a writer of the left who had an active role in society, is the subject of critical assessment in his later works, where the notion of a "presenza attiva del soggetto nella storia" gives way to the perception of "natura e storia" as "mare dell’oggettività".